Answers
Answered by
0
apply dmas
so first-> 12/6=2
then->2+10=12
now, 2-12=-10
so first-> 12/6=2
then->2+10=12
now, 2-12=-10
Answered by
0
Hey there!!
Thank you for your Question!!
Apply PEDMAS ,
![we \: have \: \\ \frac{12}{6} - 2 + 10 \\ \\ = > as \: the \: pedmas \: rule \: says \: to \: use \: the \: division \: first \: therefore \\ \\ = > 2 - 2 + 10 \\ \\ = > 2 + 8 \\ = > 10 we \: have \: \\ \frac{12}{6} - 2 + 10 \\ \\ = > as \: the \: pedmas \: rule \: says \: to \: use \: the \: division \: first \: therefore \\ \\ = > 2 - 2 + 10 \\ \\ = > 2 + 8 \\ = > 10](https://tex.z-dn.net/?f=we+%5C%3A+have+%5C%3A++%5C%5C++%5Cfrac%7B12%7D%7B6%7D++-+2+%2B+10+%5C%5C++%5C%5C++%3D++%26gt%3B+as+%5C%3A+the+%5C%3A+pedmas+%5C%3A+rule+%5C%3A+says+%5C%3A+to+%5C%3A+use+%5C%3A+the+%5C%3A+division+%5C%3A+first+%5C%3A+therefore+%5C%5C++%5C%5C+%3D++%26gt%3B++2+-+2+%2B+10+%5C%5C++%5C%5C++%3D++%26gt%3B+2++%2B+8+%5C%5C++%3D++%26gt%3B+10)
Hope this helps u!!
Thank you for your Question!!
Apply PEDMAS ,
Hope this helps u!!
Similar questions